2022
DOI: 10.1080/20002297.2022.2107814
|View full text |Cite
|
Sign up to set email alerts
|

Human periodontitis-associated salivary microbiome affects the immune response of diabetic mice

Abstract: Background The bidirectional association between periodontitis and diabetes mellitus has been well accepted; however, pathways connecting them remain unclear. Some oral bacteria are able to induce immunologic changes favoring insulin resistance individually. However, it is unclear if and how the systemic immune system responds to a disturbed oral microbial community in diabetic sufferers. Aim This study aimed to investigate the impact of the human periodontitis-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…ILC3s are involved in inflammatory bone diseases. Transfer of human periodontitis saliva to diabetic mice impairs IL17 production by ILC3s and increases osteoclasts and TNF‐α and IL‐1β levels [54] (Fig. 2D).…”
Section: Crosstalk Between Ilcs and Bone Cellsmentioning
confidence: 99%
“…ILC3s are involved in inflammatory bone diseases. Transfer of human periodontitis saliva to diabetic mice impairs IL17 production by ILC3s and increases osteoclasts and TNF‐α and IL‐1β levels [54] (Fig. 2D).…”
Section: Crosstalk Between Ilcs and Bone Cellsmentioning
confidence: 99%
“…gingivalis can manipulate the host immune system by producing virulence factors that can interfere with immune cell signaling pathways or by inducing the production of antiinflammatory cytokines, in order to maintain inflammation, obtain nutrients, and evade host immune killing. e, JZ et al found that P. gingivalis was able to interfere with the immune system and thus induce insulin resistance (He et al, 2022).…”
Section: Immune Escapementioning
confidence: 99%
“…e, JZ et al. found that P. gingivalis was able to interfere with the immune system and thus induce insulin resistance ( He et al., 2022 ).…”
Section: Pathogenesis Of Insulin Resistance Caused By P Gin...mentioning
confidence: 99%
“…We performed glucose tolerance tests after 4-week oral administration of the probiotics (Figure 1). The mice were fasted overnight and then orally administered with D-glucose by gavage (2 g/kg, n = 3 for each group) [20,21], which was dissolved in 20 mM PBS (10% D-glucose, pH 7.0). Blood glucose levels were measured by using a blood glucose meter (Yicheng, Beijing, China).…”
Section: Oral Glucose Tolerance Test (Ogtt)mentioning
confidence: 99%